Effect of underwater swimming on physiological and perceptual parameters in elite swimmers in normoxia and altitude hypoxia conditions - Guimard, A.; de la Fuente, B.; Segovia, C.; Gonzalez-Frutos, P.; Veiga, S. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Nowadays, the underwater swimming is commonly used by swimmers, to the point of becoming a central element in competition. In competition, swimmers spend a large part of the races swimming underwater (Pla et al., 2021). Obviously, when the swimmers are underwater, they are in apnea and is therefore confronted with a well-known reflex called the diving response. Apnea response is known to preserve oxygen store to avoid hypoxia-induced cardiac and brain damage (Alboni et al., 2011). In swimming, it has also been shown that apnea effort is logically perceived as harder when swimming on the surface at the pace of a 400 m race (compared to normal breathing) (Guimard et al., 2018) and when increasing the number of undulatory kicks in underwater (Veiga et al., 2022). [...]